1993
DOI: 10.1007/bf00119435
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of herbicides on primary productivity of periphyton in lotic environments

Abstract: : Freshwater algae are quite sensitive to herbicides that enter running water ecosystems through direct application, aerial drift, and/or watershed run-off. However, due to a lack of suitable methodologies, few studies examine the effects of such contamination on naturally occurring attached algal communities under field conditions (i. e., exposure regimes using pulsed doses or brief episodes of peak concentrations to simulate surface run-off during storm events). This paper describes a method for determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…1) indicative of strong outflow, stratification may also fail to develop although much depends on the intensity and duration of flow. Thus, there appears to be little difference in the whole lake ecosystem rate of respiration before and after recovery from the application of herbicide in agreement with the results of Day (1993). However, there is a noticeable long-term trend in the pattern of R with time that likely reflects a transition to autumnal senescence and the inherent variability in this pond ecosystem.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…1) indicative of strong outflow, stratification may also fail to develop although much depends on the intensity and duration of flow. Thus, there appears to be little difference in the whole lake ecosystem rate of respiration before and after recovery from the application of herbicide in agreement with the results of Day (1993). However, there is a noticeable long-term trend in the pattern of R with time that likely reflects a transition to autumnal senescence and the inherent variability in this pond ecosystem.…”
Section: Methodssupporting
confidence: 86%
“…For example, the effects of low-concentration atrazine exposure of periphyton were examined under laboratory conditions and found to significantly impact productivity (Kosinski, 1984;Hamala and Kollig, 1985;Lynch et al, 1985;Krieger et al, 1988). Day (1993) investigated the impact of several herbicides on lotic periphyton productivity using 0.33-4 h chamber incubations and concluded there are significant effects on productivity although net respiration was not significantly affected by 3 of 4 compounds investigated. Girling et al (2000a) evaluated minimum effective concentrations for several herbicides as a function of species and Girling et al (2000b) compiled information for evaluating toxicity of various chemicals in freshwater systems.…”
Section: Introductionmentioning
confidence: 98%
“…The association of metolachlor with increased autotrophic growth is unclear. Atrazine typically has been found to inhibit algal growth more than metolachlor (e.g., Day 1993;Fairchild et al 1998;Kotrikla et al 1999), which our data supports. However, there is little evidence of growth stimulation of algae by metolachlor in the literature.…”
Section: Pollutant Interactionssupporting
confidence: 87%
“…Algal species can have varying levels of susceptibility Tang et al 1998;Lockert et al 2006;Murdock and Wetzel 2012), higher light intensity can make algae more susceptible (Guasch et al 1997(Guasch et al , 2003, and previous exposure can lessen the negative impacts of future exposures (Knauert et al 2008;Tlili et al 2011). Further complicating the ability to predict periphyton community response to runoff is that atrazine concentrations are often not uniform in space or time (Kolpin and Kalkhoff 1993;Solomon et al 1996), and atrazine binding within photosystem II is reversible, with chloroplast functional recovery possible within hours of atrazine removal (Day 1993).…”
Section: Introductionmentioning
confidence: 99%
“…There are also a few reports on the joint effects of herbicides on algal communities in model streams (Kosinski 1984;Krieger et al 1988). The results of short (4 h)-and long (3-14 d)-term toxicity tests with the green alga, Selenastrum capricornutum, have been compared and it was suggested that the former can be used to complement information gained in the latter (Versteeg 1990 responses of periphyton to herbicides under field conditions by monitoring changes in oxygen production has been reported (Day 1993).…”
Section: Introductionmentioning
confidence: 99%